A low power and low ripple CMOS high voltage generator for RFID transponder EEPROM - Rahman L.F.; Marufuzzaman M.; Alam L.; Sidek L.M.; Reaz M.B.I. (Public Library of Science, 2023)
Article; controlled study; direct current; electric potential; energy; radiofrequency identification; simulation; software; electricity; equipment design; power supply; procedures; radio frequency identification device; radiofrequency radiation; software; transistor; Electric Power Supplies; Electricity; Equipment Design; Radio Frequency Identification Device; Radio Waves; Software; Transistors, Electronic